Evaluasi Sistem Pengelolaan Limbah B3 PT Y - Ignacia Putri Dinayah; Rizka Novembrianto (Yayasan Literasi Sains Indonesia, 2023)
Increasing the standard of living and social welfare can be marked by industrialization. Increasing industrialization has had an impact on environmental pollution caused by waste, one of which is B3 waste. PT Y is a processing industry company engaged in the production of plywood. In its production process PT Y produces B3 waste which must be managed according to the characteristics and nature of the B3 waste. B3 waste that is not managed properly will cause pollution and cause problems around it. This study aims to analyze the existing conditions regarding the management of hazardous and toxic waste (B3) from PT Y, evaluate and provide recommendations based on applicable regulations. Evaluation is carried out using the Guttman scale method to compare existing conditions with applicable regulations. The evaluation result of PT Y's B3 waste management is 66% in the